(untitled) (International Journal of Studies in Nursing, 2018)
Nurse turnover, shortages, and lack of nurse retention have all been linked to stress among nurses. This ethnographic study explored if burnout and moral distress, often a result of excessive stress, led to job turnover among critical care nurses in northern Indiana and southern Michigan. It also explored the factors that may cause burnout and moral distress in the identified population. Although burnout and moral distress have been studied in various professions and locales over the years, research specific to critical care nurses has been limited in the northern Indiana, southern Michigan area. In this study, 100% of the nurses felt that burnout and moral distress led to turnover. These same nurses attributed burnout and moral distress to affecting the quality of care given to patients. The guiding framework for this study’s design was Corley’s theory of moral distress.